Pembentukan Karakter Berwirausaha Siswa Melalui Peran Koperasi Sekolah - Triesninda - Pahlevi (Journal of Applied Business Administration, 2022)
School cooperatives do not have a legal entity but are considered as cooperative associations consisting of students, while teachers and school principals act as coaches. School cooperative activities are buying and selling goods and services. Therefore, school cooperatives are one of the media for learning entrepreneurship practices. The purpose of this study is to conduct a study to identify the role of cooperatives as forming entrepreneurial character. The research methodology used is to use a literature review or systematic literature review (SLR). The article was obtained from the search results on Google Scholar with the keywords school cooperative and entrepreneurial character. The results showed that entrepreneurial characteristics can be formed through the role of school cooperatives.